Volatile organic compound removal over bentonite-supported Pt, Mn and Pt/Mn monolithic catalysts - Colman Lerner, Jorge Esteban (2012)
The catalytic oxidation of volatile organic compounds (VOCs) (ethanol and toluene) alone and in mixture was investigated over Pt, Mn and Pt/Mn impregnated bentonite monoliths. Their properties were characterized by using the Brunauer–Emmett–Teller method, X-ray diffraction, X-ray photoelectron spectra and temperature programmed reduction (TPR). Independently of which catalyst was used, ethanol was more easily oxidized than toluene. In toluene oxidation, the sequence of catalytic activity was as follows: Pt/Mn/B[Pt/B[Mn/B, probably due to some favorable synergetic effects between Pt and Mn and to the presence of Mn3+/Mn4+ species. In ethanol oxidation, Pt/Mn/B and Pt/B present similar activities, and greater than that of Mn/B. In the VOC mixture, toluene slows down the partial oxidation of ethanol towards acetaldehyde. On the contrary, the presence of ethanol has a promoting effect on toluene oxidation.